Tensile bond strength of a soft liner to an acrylic resin after primer application and thermocycling - Goiato, Marcelo Coelho [UNESP]; Dos Santos, Daniela Micheline [UNESP]; De Medeiros, Rodrigo Antonio [UNESP]; Filho, Aljomar José Vechiato [UNESP]; Sinhoreti, Mário Alexandre Coelho; Da Silva, Emily Vivianne Freitas [UNESP]; Moreno, Amália [UNESP] (FapUNIFESP (SciELO), 2015)
Purpose: The aim of this study was to evaluate the effect of a surface treatment with Sofreliner primer on tensile bond strength of a resin-based soft liner (Coe-Soft) bonded to a polymethylmethacrylate (PMMA) resin before and after accelerated aging simulated by a thermocycling machine. Material and Methods: One hundred and twenty rectangular specimens of PMMA resin were fabricated with 10 10 mm of cross-section and 40 mm of height. The resin-based soft liner was positioned between two PMMA resin specimens. The specimens were divided randomly into 6 groups (n = 10) accorDing to the surface treatment and accelerated aging cycles (0, 500 and 1000). After accelerated aging, specimens were submitted to tensile bond strength test. The fractures were classified as adhesive, cohesive or both. Results: Most failures were classified as cohesive (p = 0.025) and there was an increase on the mean values of tensile bond strength for group with primer application regardless the cycles of accelerated aging, and also an increase along thermocycling periods. The scanning electronic microscopy was used to illustrate the types of failures and the effect of primer application on PMMA acrylic resin surface. Conclusion: The primer application associated with resin-based soft liners is clinically viable, once this treatment strategy provides a reliable adhesion.
Keywords: Acrylic resins; Adhesion; Denture liners; Primers and coupling agents; Surface treatment